The Postwar Stability of the Fisher Effect - PEEK, JOE; WILCOX, JAMES A. (Journal of Finance, 1983)
ABSTRACT Most research concerning the Fisher relationship has concentrated on the magnitude and significance of the response of nominal interest rates to anticipated inflation. Recently, attention has shifted to the stability of that response. According to previous estimates, the impact of anticipated inflation on interest rates varies substantially over time. By extending a standard model to include tax and aggregate supply shock effects, we are able to reduce such instability considerably. Our results also reveal that increased foreign demand for bonds lowers the interest rate.